PERANCANGAN SISTEM INFORMASI STOCK COMPOUND BERBASIS WEBSITE DENGAN PENDEKATAN UNIFIED MODELLING LANGUAGE - Susilawati, Dera; Zohari, Ahmad; Ali Darmawan, Ferdy; Wahyu Sudrajat, Danar (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
PT RCI faces challenges in managing FIFO stock compound information in the mixing department, the system currently used is still manual with a coin board as a tool for recording and visualizing data. This condition makes it difficult to monitor stock in real time, increases the risk of compound taking errors, and takes a long time to update data every day. To overcome this problem, this study designs a website-based stock information system using UML (Unified Modeling Language) as a visual modeling language to make it easier for users to understand and interact with the system. UML design is carried out as an initial step before website development begins. This system is designed to make the process more efficient and structured. The UML used includes 4 types of diagrams, namely Use Case Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. The design of a website- based stock information system was successfully built using UML, which involved 2 actors, namely: Operator and Staff.